2020
DOI: 10.3390/jpm10040224
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Deep Convolutional Neural Networks to Brain Cancer Images: A Survey

Abstract: In recent years, improved deep learning techniques have been applied to biomedical image processing for the classification and segmentation of different tumors based on magnetic resonance imaging (MRI) and histopathological imaging (H&E) clinical information. Deep Convolutional Neural Networks (DCNNs) architectures include tens to hundreds of processing layers that can extract multiple levels of features in image-based data, which would be otherwise very difficult and time-consuming to be recognized and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…We have previously shown that DCNN models can be trained and applied to TCGA H&E histopathological images to predict brain cancer patient survival 46 (see also review in ref. 47 ). To analyse the relationship between segmentation results and patient survival, we next performed Pearson correlation analysis between the area of different brain tumour regions and patient survival across (i) all TCGA glioblastomas, and (ii) brain tumours harbouring the 13 most frequent mutations (PTEN, TP53, EGFR, NF1, PIK3CA, PI3KR1, TRAPP, ATRX, PDGFRA, KMT2C, PB1, GRIN2A, IDH1; see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that DCNN models can be trained and applied to TCGA H&E histopathological images to predict brain cancer patient survival 46 (see also review in ref. 47 ). To analyse the relationship between segmentation results and patient survival, we next performed Pearson correlation analysis between the area of different brain tumour regions and patient survival across (i) all TCGA glioblastomas, and (ii) brain tumours harbouring the 13 most frequent mutations (PTEN, TP53, EGFR, NF1, PIK3CA, PI3KR1, TRAPP, ATRX, PDGFRA, KMT2C, PB1, GRIN2A, IDH1; see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A complete image classification model is a combination of convolutional and non-linearity layers, followed by several fully connected layers. With this architecture a number of models have been proposed, such as AlexNet (2012), ZF Net (2013), GoogLeNet (2014), VGGNet (2014), ResNet (2015), DenseNet (2016) (Khan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers and readers who are interested in further papers on brain tumor classification using CNN can examine the following review articles (Litjens et al 2017 ; Lotan et al 2019 ; Muhammad et al 2021 ; Shaver et al 2019 ; Shirazi et al 2020 ; Tandel et al 2019 ; Tiwari et al 2020 ), which are very rich resources on this topic.…”
Section: Related Workmentioning
confidence: 99%